Testing the Concept of Mitigating Overflowing Urban Drain with Permeable Road - Mah, D.Y.S.; Bustami, R.; Putuhena, F.J.; Dianty, M.A. (The World Academy of Research in Science and Engineering, 2020)
This study describes a new idea of allowing the overflowing urban drains that cause flash flooding to be connected to a permeable road structure beside the drain. The permeable road with water storage/convey structure could soak up the spill-over waters from drains. In this regard, the Storm Water Management Model (SWMM) was utilized to assist the investigation by simulating a historical flood event with a total rainfall of 324 mm over 5200 m2 of commercial area. It was expected to generate 1685 m3 of surface runoff. The model provided an insight that reducing the flood event’s peak discharge by half would require to have a spill-over space of 640 m3 in the permeable road with a surface area of 1600 m2 and a depth of 0.40 m. This allowed a guide to the selection of suitable products to construct the permeable road.